Candida auris: a novel emerging nosocomial pathogen - properties, epidemiological situation and infection control - Caliman Sato, Marcelo; Izu Nakamura Pietro, Emilene Cristine; Marques da Costa Alves, Lucas; Kramer, Axel; da Silva Santos, Paulo Sérgio (German Medical Science GMS Publishing House, 2023)
Immunosuppression and critical illnesses in combination with ecological imbalance open the door for novel opportunistic fungal infections, as in case of . has emerged globally as a multidrug-resistant yeast, causing infections and outbreaks in health care facilities. This narrative review discusses the properties of the yeast, the development of the epidemiological situation, the nosocomial spread and causes for nosocomial outbreaks triggered by in the hospital environment, and summarizes international recommendations for infection control, supplemented by suggestions on diagnostic, screening and antibiotic stewardship.